2008
DOI: 10.1177/112067210801800126
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Optic Disc Pit Associated Maculopathy

Abstract: Serous retinopathy associated with optic disc pit responds well to early vitrectomy, endolaser, and internal tamponade. Silicone oil was effective in one refractory case. Cumulative data are required to define the management of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 22 publications
0
33
0
1
Order By: Relevance
“…Differences in techniques result from the selection of adjuvant procedures such as short or long-acting gas tamponade, ILM peeling, endolaser photocoagulation in the peripapillary area and drainage of subretinal fluid. [27][28][29][30]33,[35][36][37][40][41][42][43][44][45][46][47] Hirakata et al 22 reported favourable results in 10 out of 11 patients treated with vitrectomy and gas exchange without endolaser photocoagulation. Hirakata et al 36 have also recently reported good surgical outcomes with vitrectomy but without laser treatment or gas tamponade for macular detachment with an optic disc pit.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in techniques result from the selection of adjuvant procedures such as short or long-acting gas tamponade, ILM peeling, endolaser photocoagulation in the peripapillary area and drainage of subretinal fluid. [27][28][29][30]33,[35][36][37][40][41][42][43][44][45][46][47] Hirakata et al 22 reported favourable results in 10 out of 11 patients treated with vitrectomy and gas exchange without endolaser photocoagulation. Hirakata et al 36 have also recently reported good surgical outcomes with vitrectomy but without laser treatment or gas tamponade for macular detachment with an optic disc pit.…”
Section: Discussionmentioning
confidence: 99%
“…The previous case series concentrated mostly on the surgical procedure, the success rate and the improvement of BCVA after treatment [17][18][19]22]. The studies published thus far, however, have not reported changes in visual function in association with the postoperative foveal structure during the follow-up period.…”
Section: Discussionmentioning
confidence: 92%
“…Several case series report resolution of subretinal fluid and improvement in the BCVA after pars plana vitrectomy (PPV) [17][18][19][20][21][22], scleral buckle (SB) [23,24], or other surgical modalities [25]. It has to be mentioned that laser photocoagulation alone has also been used, with variable success [16].…”
Section: Introductionmentioning
confidence: 96%
“…Several factors related to retinal detachment associated with congenital pit of the optic disc are noteworthy. First, good visual recovery is possible even months after the onset of maculopathy (19) , and serous macular retinal detachment responds well to early vitrectomy (20) . Macular detachments associated with pits of optic disc occur in young patients, who usually do not have significant vitreous liquefaction, which, in turn, makes less likely the hypothesis that the liquid comes from the vitreous (21) .…”
Section: Discussionmentioning
confidence: 99%